2010
DOI: 10.1021/ie901370w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alkali Vapor Exposure on Ni-MgO/γ-Al2O3/Cordierite Monolithic Catalyst for Biomass Fuel Gas Reforming

Abstract: Fly ash compounds, such as alkali salts, in the raw biomass fuel gas can contaminate and deposit on traditional granular Ni-based catalysts, which resulted in catalyst deactivation and pressure increase of the downstream reformer. The impact of alkali salt exposure (KCl, K 2 SO 4 , K 2 CO 3 , by evaporation at about 7.8 mg/L for 6 h) on dry CH 4 /CO 2 reforming of model biomass fuel gas (H 2 /CO/C 2 H 4 /CH 4 /CO 2 / N 2) 15.8/12.1/2.51/ 15.0/22.1/32.6 vol %) over Ni-MgO/γ-Al 2 O 3 /cordierite monolithic catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Ethene was completely converted in all cases (not shown), probably reflecting the fate of other reactive components at these conditions, as also found by Li et al [15]. For all temperatures and catalysts a higher CH 4 conversion is achieved at elevated S/C ratios.…”
Section: Effect Of Steam Partial Pressuresupporting
confidence: 85%
See 1 more Smart Citation
“…Ethene was completely converted in all cases (not shown), probably reflecting the fate of other reactive components at these conditions, as also found by Li et al [15]. For all temperatures and catalysts a higher CH 4 conversion is achieved at elevated S/C ratios.…”
Section: Effect Of Steam Partial Pressuresupporting
confidence: 85%
“…Albertazzi et al [33] exposed a Ni-based catalyst to gas from a lab-scale gasifier and observed loss in the reforming activity, but also reported that the activity was regained during the reforming process, presumably the alkali was washed off the catalyst surface. Li et al [15] exposed a monolithic Ni-based catalyst to alkali salt vapors (KCl, K 2 SO 4 , K 2 CO 3 ) and found a general deactivation of the reforming reaction. Physical characterization revealed severe loss of surface area of the catalyst.…”
Section: Effect Of Potassium Salt Depositionmentioning
confidence: 99%
“…Addition of potassium to a Ni-based catalyst resulted in the increase of hydrogen production from biomass thermo-chemical conversion [34,35]. The negative effect of the presence of alkali metal on hydrogen production from biomass thermo-chemical conversion has been reported by Wu et al [36] who found that H2 content decreased from 35.1 to 26.7% when alkali metal vapors exposed over catalyst for 17 hours during the catalytic reforming of biomass fuel gas.…”
Section: Introductionmentioning
confidence: 78%
“…The many related reports of alkali or alkaline earth metal promoted catalysts in the literature have been summarized by Hu and Ruckenstein. [28][29][30][31][32] CO 2 adsorption can be significantly enhanced over Ni catalysts that incorporate basic metal oxides, which is very helpful for the inhibition of carbon formation. [28][29][30][31][32] CO 2 adsorption can be significantly enhanced over Ni catalysts that incorporate basic metal oxides, which is very helpful for the inhibition of carbon formation.…”
Section: Promotersmentioning
confidence: 99%